2021
DOI: 10.3390/buildings11080319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating 4D-BIM and VR for Effective Safety Communication and Training: A Case Study of Multilingual Construction Job-Site Crew

Abstract: Effective safety management is a key aspect of managing construction projects. Current safety management practices are heavily document-oriented that rely on historical data to identify potential hazards at a construction job site. Such document-bound safety practices are prone to interpretative and communication errors in multilingual construction environments, such as in the United Arab Emirates (UAE). Applications of Building Information Models (BIM) and Virtual Reality (VR) are claimed to improve hazards i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 81 publications
2
21
0
1
Order By: Relevance
“…In multinational projects, migrant construction workers from several national origins will work on the same site (Oswald et al, 2019). Although middle and senior managers often communicate in English, communication between migrant construction workers at the lower ranks is often complex and could include the use of languages as diverse as Mandarin, Urdu and Hindi (Afzal and Shafiq, 2021). This results in commands or safety instructions having to be translated into multiple languages, which is a complex and error-prone process that greatly increases the safety risk on the construction site (Afzal and Shafiq, 2021).…”
Section: Ecam 313mentioning
confidence: 99%
“…In multinational projects, migrant construction workers from several national origins will work on the same site (Oswald et al, 2019). Although middle and senior managers often communicate in English, communication between migrant construction workers at the lower ranks is often complex and could include the use of languages as diverse as Mandarin, Urdu and Hindi (Afzal and Shafiq, 2021). This results in commands or safety instructions having to be translated into multiple languages, which is a complex and error-prone process that greatly increases the safety risk on the construction site (Afzal and Shafiq, 2021).…”
Section: Ecam 313mentioning
confidence: 99%
“…The findings of this study indicated that the proposed VR method could reduce the time spent on HR compared to traditional methods. Similarly, several studies (e.g., [27]) adopted the immersive VR method for HR at construction workplaces. The immersive VR method has also been widely used to train and educate about SO (8 documents), followed by SA (5 documents).…”
Section: Immersive Trainingmentioning
confidence: 99%
“…However, both Expert B and C claimed that skills enhancement cannot be achieved overnight, and practical measures toward B9 and B10 deserve to be adopted to break the loop closure. Specifically, Afzal and Shafiq (2021) advised that an open and repeatable workflow is expected to solve B10 (strategy 8) so that ineffective sharing like replaceable, repetitive or missing cases will be significantly avoided, and the Standardization level could be improved (Chang et al, 2020). Besides, Expert M proposed to utilize more affective computing methods to record users' objective feelings (e.g.…”
Section: Strategymentioning
confidence: 99%